Gifts of writing creative projects with words and art - Tchudi, Susan J. (Susan Jane) 1945-; Tchudi, Stephen 1942- (New York Scribner, 1980)
Gives suggestions for combining creative writing, calligraphy, and art work to produce unique and personal gifts such as stationery, postcards, posters, greetings cards, books of several types, and holiday projects.
Keywords: Handicraft; Authorship; Calligraphy; Books